Another Global Paradox : The Impact of China's "One Cbild" Planned Bird Policy - Tulus Warsito (FISIP UMY, 2015)
More lhan one quarler ot cenlury has passed since lhe Filst lnternational Populalion Conference was held in Bucharest rn 1974, the govemment ol each nalion and lhe intemational community as a whole have made new progress in imple. menting the World Populalion Plan of Action and The [4exico City oeclaralion 1984. The rale of increase in wo d populalion has been lurther slowed. So lar, world population still continues to increase 90 million per annum, to reach 6,5 billion by lhis yea(2006) and will probabt get 8,4 brllion by 2015 As lhe